Home births in Portugal - Santos, Mário (Home birth - Options, Practices and Organisations in Denmark (COST IS0907 Short Term Scientific Mission), 2014)
Home births were part of the action of curious women, someone we could call informal midwives, a respect person and central in the community. Until the 70’s there was a big tradition in home births in Portugal. In 1961, 80% of all births where at home. But the perinatal mortality rate in 1975 was 31,8 for 1.000 women. This is a strong argument always brought up when speaking of home births. However, better hygiene, better education, better access to health care, better antenatal care had an important part to play. And this argument misses to see the morbidity or the long term effects of the hospitalization of birth and the overuse of interventions: in 2011, half of the births where instrumental (vacuum, forceps or c-sections - 52%) and 36% of these were caesarean sections.